Mathematical Modeling of Typhoid Fever Control Through Non-Pharmaceutical Interventions in South Sulawesi - Fausiatul Iffa; Wahidah Sanusi; Alimuddin Alimuddin (Jurusan Matematika FMIPA UNM, 2026)
Typhoid fever remains one of the major public health problems in Indonesia, particularly in South Sulawesi. This article discusses mathematical modeling of the impact of non-pharmaceutical interventions on typhoid fever control. This study aims to develop a mathematical model that represents the dynamics of typhoid fever transmission and to solve the model numerically using the Variational Iteration Method (VIM). The model applied is the SICRB compartment model, which divides the population into five groups: susceptible (S), infected (I), chronic carrier (C), recovered (R), and bacterial concentration (B). The analysis results indicate that the basic reproduction number R₀ > 1, suggesting that typhoid fever has the potential to persist in the population. Numerical simulations are carried out using Maple for analytical derivation and R Studio for visualization of the dynamics. The implementation of non-pharmaceutical interventions, including health education, environmental sanitation, and herbal treatment, demonstrates a significant reduction in infection cases, an increase in recovery, and a decrease in bacterial concentration. The model shows stability toward the endemic equilibrium and consistency between mathematical analysis and numerical simulations.